2019
DOI: 10.3892/etm.2019.7424
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of microRNA expression between patients with and without latent tuberculosis infections

Abstract: Tuberculosis (TB) is a globally prevalent infectious disease. The mechanisms of latent TB infection (LTBI) remain to be fully elucidated and may provide novel approaches for diagnosis. As therapeutic targets and molecular diagnostic markers, microRNAs (miRs) have been studied and utilized in various diseases. In the present study, the differentially expressed miRs (DEMs) in LTBI were screened and analyzed to determine the underlying mechanisms and identify potential biomarkers, thereby contributing to the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…PTEN has been documented to play a key role in resisting infections by bacillus Calmette-Guérin and Mycoplasma in mammalian cells [ 21 ]. In a work by Lu et al ., PTEN was identified as one of the four key factors mediated by the differentially expressed microRNAs between patients with and without latent tuberculosis infections [ 36 ]. However, the specific role of PTEN in Mtb infection remains unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN has been documented to play a key role in resisting infections by bacillus Calmette-Guérin and Mycoplasma in mammalian cells [ 21 ]. In a work by Lu et al ., PTEN was identified as one of the four key factors mediated by the differentially expressed microRNAs between patients with and without latent tuberculosis infections [ 36 ]. However, the specific role of PTEN in Mtb infection remains unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the ubiquitous use of pathway analysis methods and reliance on their output to interpret results from diverse and important fields of research such as drug development ( Jhamb et al, 2019 ), biomarker discovery ( Chen et al, 2017 ) and patient diagnosis ( Lu et al, 2019 ), it is important to ensure that these methods can cope well with complex gene sets.…”
Section: Introductionmentioning
confidence: 99%
“…During MTB infection, which lies at the root of active TB disease in humans, downregulated expression of microRNAs homo sapiens (hsa)-miR-29a and hsa-miR-15b has been reported [4]. By contrast, hsa-miR-576-5p, hsa-miR-500 and hsa-miR-155 expression have been shown to be upregulated during latent tuberculosis infection (LTBI) [3]. Intriguingly, miRNA effects have been demonstrated during different stages of TB progression; for example, Beibei Fu et al found that miR-325-3p was upregulated after MTB infection then demonstrated that miR-325-deficient mice exhibited MTB resistance [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, host molecular regulatory mechanisms, such as gene-expression regulation by microRNAs (miRNAs), may also be involved in disease progression. As a class of non-coding ribonucleic acids (RNAs),miRNAs play key roles in regulating post-transcriptional gene expression during numerous physiological and pathological processes, including MTB infection and TB progression to active disease [3]. During MTB infection, which lies at the root of active TB disease in humans, downregulated expression of miRNAs homo sapiens (hsa)-miR-29a and hsa-miR-15b has been reported [4].…”
Section: Introductionmentioning
confidence: 99%